Analisis Biaya - Volume - Laba Sebagai Dasar Target Laba Yang Ingin Dicapai - Valentina Monoarfa (Mopolayio : Jurnal Pengabdian Ekonomi, 2022)
Cost-volume-profit (CVP) analysis is one of several very useful tools for managers in giving orders. The purpose of the research on these five tofu industries is to analyze the cost of profit volume as the basis for the profit target to be achieved by the tofu industry presented by several tofu and tempeh factories in Gorontalo, namely to provide information on how to analyze the cost-volume-profit by using this technique. algebra, graphic engineering, and trial and error calculation techniques. The research method used by the author is a descriptive approach, which is a research procedure that produces descriptive data in the form of written and spoken words from research informants and the behavior of the observed object of research. The results show that the cost-volume-profit analysis is often simply described as a break-even analysis. However, companies must also realize that break-even analysis is the key to cost-volume-profit analysis. The researcher chose the Teenage Tofu Tempe Factory Work I”, “Mbak Sri Tofu Factory, “Blessing Tempeh Tofu Factory” and “Rina Tofu Tempe Factory as research locations. Researchers get information about problems at the location of the production process. The owner does not take into account all production costs in setting the cost of goods sold so that profits cannot reach the target.